Valoración funcional pre y postquirúrgica en pacientes sometidos a artroplastia total de cadera en el Hospital Manuel Ygnacio Monteros de la ciudad de Loja, periodo enero - octubre. - Herrera Jaramillo, Edgar (2014)
This research work is an evaluative study of pre and post surgical functionality of the patients who underwent Total Hip Arthroplasty in the "Manuel Ygnacio Monteros" Hospital, in 2013, discusses issues related to: Ranges movement and mobility; walk and manifestation of pain, using the test of functionality or Harris Score (HHS). It is a descriptive, prospective research work, cross type, comparing results in a single population before and after hip arthroplasty. 32 patients was evaluated during the period of 10 months using Scale Harris functionality. Individual evaluation before surgery and 24 hours postoperative was performed. The main objective was to compare clinical and functionally, both the pre and post surgical aspect for patients subjected to Total Hip Arthroplasty in the "Manuel Valdivieso Ygnacio Monteros" Hospital through functional scales and mobility ranges. Addition to: To determine the existence of variations in mobility ranges pre and post surgically in patients undergoing total hip arthroplasty. Determine Functional Differences Pre and post surgical patients undergoing total hip arthroplasty. Establish differences between radiological diagnosis and functionality in patients with clinical coxarthrosis. Determine the age group and genus presentation more coxarthrosis Evaluate clinical differences between the sexes functional improvement of patients undergoing total hip arthroplasty. Describe the immediate criteria for functional improvement in patients undergoing total hip arthroplasty. Criteria of trust to establish the functional scales in patients candidates Hip Arthroplasty Results: Grade IV (47%) and Grade III osteoarthritis (44%) were the diagnoses with the highest incidence in patients undergoing hip arthroplasty. Sorted by Harris Scale 97% of patients have surgically evaluated pre malfunction, the remaining 3% have a failed function. Considering the Harris score, the same ranging from 0 to 100, patients evaluated in this study presents a timely preoperative average of 52.7., Equivalent to BAD JOB. The average or mean of our post surgical patients was equivalent to 77.6 FUNCTION FAILED. Disaggregated way, post surgical percentages were: Malfunction (6%). Function failed (50%). Good function (41%). Excellent function 3%. Conclusion: Functional Scale Harris, value ranges and mobility aspects such as running, distance, use of walking aid. It is a reliable instrument. In our study, in the post surgical evaluation at 24 hours, shows that the clinical signs of pain is the first evaluation item that improves postoperatively. Other aspects are ranges that improve functionality of the hip joint and flexion, internal and external rotation. Keywords: Functional Scale Harris Hip Arthroplasty, improving function.